DIGITAL TRANSFORMATION OF INFORMAL EDUCATIONAL INSTITUTIONS IN THE FRAMEWORK OF THE TRIDHARMA OF HIGHER EDUCATION: A META-SYNTHESIS ANALYSIS - Apriyudin Apriyudin; Reti Sri Haryati; Nina Nurlina; Siti Salbiah; Muhammad Wachid Suryo Putro; RR. Andriani Sariwardani (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
The purpose of this study is to analyse how digital transformation in informal educational institutions is integrated and supported through the three pillars of the Tridharma of Higher Education (Education, Research, and Community Service). This research uses a qualitative meta-synthesis of 10 selected research articles published over the last 10 years (2016–2026). The data selection process is carried out through a systematic review to identify patterns, challenges, and digitalisation strategies. The findings show that digital transformation in informal institutions is evolving from simply using blended learning to adopting intelligent technologies such as AI and the Metaverse. Higher education institutions play a crucial role in closing the digital literacy gap through community service schemes and the development of innovative learning media. However, the main obstacles remain in human resources and digital quality standards. Conclusion: Synergy between higher education institutions and informal institutions within the Tridharma framework is the main key to the sustainability of the non-formal education ecosystem in the digital era.